Accuracy of an HRP-2/panLDH rapid diagnostic test to detect peripheral and placental Plasmodium falciparum infection in Papua New Guinean women with anaemia or suspected malaria. (December 2015) - Umbers, Alexandra; Unger, Holger; Rosanas-Urgell, Anna; Wangnapi, Regina; Kattenberg, Johanna; Jally, Shadrach; Silim, Selina; Lufele, Elvin; Karl, Stephan; Ome-Kaius, Maria; Robinson, Leanne; Rogerson, Stephen; et al.
Abstract Background The diagnosis of malaria during pregnancy is complicated by placental sequestration, asymptomatic infection, and low-density peripheral parasitaemia. Where intermittent preventive treatment (IPT) with sulfadoxine-pyrimethamine is threatened by drug resistance, or is inappropriate due to low transmission, intermittent screening and treatment (ISTp) with rapid diagnostic tests for malaria (RDT) could be a valuable alternative. Therefore, the accuracy of RDTs to detect peripheral and placental infection was assessed in a declining transmission setting in Papua New Guinea (PNG). Methods The performance of a combination RDT detecting histidine-rich protein-2 (HRP-2) andPlasmodium lactate dehydrogenase (pLDH), and light microscopy (LM), to diagnose peripheralPlasmodium falciparum andPlasmodium vivax infections during pregnancy, were assessed using quantitative real-time PCR (qPCR) as the reference standard. Participants in a malaria prevention trial in PNG with a haemoglobin ≤90 g/L, or symptoms suggestive of malaria, were tested. Ability of RDT and LM to detect active placental infection on histology was evaluated in some participants. Results Among 876 women, 1162 RDTs were undertaken (anaemia: 854 [73.5 %], suspected malaria: 308 [26.5 %]). qPCR detected peripheral infection during 190 RDT episodes (165P. falciparum, 19P. viva x, 6 mixed infections). Overall, RDT detected peripheralP. falciparum infection with 45.6 % sensitivity (95 % CI 38.0–53.4), a specificity of 96.4 % (95.0–97.4), a positive predictive value of 68.4 % (59.1–76.8), and a negative predictive value of 91.1 % (89.2–92.8). RDT performance to detectP. falciparum was inferior to LM, more so amongst anaemic women (18.6 vs 45.3 % sensitivity, Liddell's exact test, P < 0.001) compared to symptomatic women (72.9 vs 82.4 % sensitivity, P = 0.077). RDT and LM missed 88.0 % (22/25) and 76.0 % (19/25) ofP. vivax infections, respectively. In a subset of women tested at delivery and who had placental histology (n = 158) active placental infection was present in 19.6 %: all three peripheral blood infection detection methods (RDT, LM, qPCR) missed >50 % of these infections. Conclusions In PNG, HRP-2/pLDH RDTs may be useful to diagnose peripheralP. falciparum infections in symptomatic pregnant women. However, they are not sufficiently sensitive for use in intermittent screening amongst asymptomatic (anaemic) women. These findings have implications for the management of malaria in pregnancy. The adverse impact of infections undetected by RDT or LM on pregnancy outcomes needs further evaluation.